Analisa Faktor-Faktor Pengaruh Minat Beli Paket Data Telkomsel Dengan Masa Pandemi Covid 19 Sebagai Variabel Moderating - Astri Mariana Isniawati; Muhammad Jalari (Entrepreneurship Faculty, Universitas Garut, 2021)
Abstract– The purpose of this study is to find out what factors influence the interest in buying telkomsel data packages with the covid 19 pandemic as a moderation variable. The type of population in this study is an unlimited population. Data collection techniques use non probability techniques on purposive sampling types. Data collection was conducted by the method of disseminating questionnaires and samples of 70 respondents. The data analysis technique used is multiple linear regression analysis using SPSS version 19. The result of this study is that the quality of the product does not have a significant effect on the purchase interest of telkomsel data package, the brand image has a significant effect on the purchase interest of telkomsel data package, the advertisement does not have a significant effect on the purchase interest of telkomsel data package, during the covid 19 pandemic it has a significant effect on the buying interest of telkomsel data package. Keywords: Product Quality, Brand Image, Price, Advertising, During the Covid 19 Pandemic, Interest in Buying Telkomsel Data Package